2021
DOI: 10.1111/eth.13139
|View full text |Cite
|
Sign up to set email alerts
|

Pairing status moderates both the production of and responses to anti‐parasitic referential alarm calls in male yellow warblers

Abstract: Defending offspring incurs temporal and energetic costs and can be dangerous for the parents. Accordingly, the intensity of this costly behavior should reflect the perceived risk to the reproductive output. When facing costly brood parasitism by brown‐headed cowbirds (Molothrus ater), where cowbirds lay eggs in heterospecific nests and cause the hosts to care for their young, yellow warblers (Setophaga petechia) use referential “seet” calls to warn their mates of the parasitic danger. Yellow warblers of both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
1
11
1
Order By: Relevance
“…However, cowbird presence during cowbird playbacks did not statistically covary with whether warblers seet called in response to the chatter playback (Fisher's exact test, p = .37), indicating that cowbird chatters, like cowbird models, are a suitable stimulus to experimentally simulate cowbirds. Female warblers seet called equally during cowbird chatter playbacks than during seet playbacks, but in our playback study with male yellow warblers (Lawson et al, 2021), we found that males seet called at a higher rate towards cowbird chatters compared to seet call playbacks. Personal (private) information (sensu Thorogood & Davies, 2012) about brood parasitism risk, such as directly seeing or hearing the brood parasite, can offer greater reliability of the threat compared to social information obtained from assessing cowbird presence based on seet calls from neighbors.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…However, cowbird presence during cowbird playbacks did not statistically covary with whether warblers seet called in response to the chatter playback (Fisher's exact test, p = .37), indicating that cowbird chatters, like cowbird models, are a suitable stimulus to experimentally simulate cowbirds. Female warblers seet called equally during cowbird chatter playbacks than during seet playbacks, but in our playback study with male yellow warblers (Lawson et al, 2021), we found that males seet called at a higher rate towards cowbird chatters compared to seet call playbacks. Personal (private) information (sensu Thorogood & Davies, 2012) about brood parasitism risk, such as directly seeing or hearing the brood parasite, can offer greater reliability of the threat compared to social information obtained from assessing cowbird presence based on seet calls from neighbors.…”
Section: Discussioncontrasting
confidence: 79%
“…Numerous published replication and pivoting experimental studies in the yellow warbler/brownheaded cowbird system have led to an integrated understanding of the seet call as a referential alarm call used in antiparasitic nest defense and the socio-environmental contexts that promote its use (see Appendix). Together with our recent works (Lawson et al, 2020(Lawson et al, , 2021, our study here is amongst the first to use solely acoustic stimuli to compare female yellow warblers' aggressive responses towards a full series of brood parasite, nest predator, and conspecific alarm vocalizations. Indeed, previous studies in this system used mostly either combinations of acoustic/visual stimuli or only visual stimuli.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Once hatched, the brood parasitic chicks greatly reduce the breeding success of the hosts, by outcompeting the hosts' offspring or by killing their nestmates altogether (Davies, 2000). Therefore, hosts have evolved multifaceted defenses to avoid being parasitized (Feeney et al, 2012;Welbergen & Davies, 2009), such as building highly concealed nests (Jelínek et al, 2014;Mérő & Žuljević, , 2019, gathering social information regarding the presence of brood parasites (Lawson et al, 2020(Lawson et al, , 2021Thorogood & Davies, 2012, and by mobbing adult brood parasites (Požgayová et al, 2009;Trnka et al, 2013). Brood parasites bypass these defenses by fast egg-laying (Jelínek et al, 2021), color dimorphism (Thorogood & Davies, 2012), visual and acoustic mimicry (Marton et al, 2021;Trnka & Prokop, 2012;Welbergen & Davies, 2008;York & Davies, 2017), and sometimes also by retaliatory strikes and brood destruction (Soler et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Yellow warblers ( Setophaga petechia , hereafter ‘warblers’) express a suite of anti-parasitic behaviours, including referential signals [5,7]. These ‘seet’ calls refer specifically to brood parasitic brown-headed cowbirds ( Molothrus ater , hereafter ‘cowbirds’), whereas ‘chip’ calls generically alert mates to diverse predators and intruding conspecifics [5,8]. In response to experimental exposure to either parasitic stimuli (e.g.…”
Section: Introductionmentioning
confidence: 99%